Normative Bone Mineral Density Z-Scores for Canadians Aged 16 to 24 Years: The Canadian Multicenter Osteoporosis Study - Zhou, Wei (J Clin Densitom, 2010)
The objectives of the study were to develop bone mineral density (BMD) reference norms and BMD Z-scores at various skeletal sites, to determine whether prior fracture and/or asthma were related to BMD, and to assess possible geographic variation of BMD among Canadian youth aged 16–24 yr. Z-Scores were defined as the number of standard deviations from the mean BMD of a healthy population of the same age, race, and sex. Z-Scores were calculated using the reference sample defined as Canadian Caucasian participants without asthma or prior fracture. Reference standards were created for lumbar spine (L1–L4), femoral neck, total hip, and greater trochanter, by each year of age (16–24 yr), and by sex. The Z-score norms were developed for groups noted earlier. Mean Z-scores between the asthma or fracture subgroups compared with the mean Z-scores in the reference sample were not different. There were minor differences in mean BMD across different Canadian geographic regions. This study provides age, sex, and skeletal site-specific Caucasian reference norms and formulae for the calculation of BMD Z-scores for Canadian youth aged 16–24 yr. This information will be valuable to help to identify individuals with clinically meaningful low BMD.